Direct Targeting of Macrophages With Methylglyoxal-Bis-Guanylhydrazone Decreases SIV-Associated Cardiovascular Inflammation and Pathology. (15th April 2017) - Walker, Joshua A.; Miller, Andrew D.; Burdo, Tricia H.; McGrath, Michael S.; Williams, Kenneth C.
Abstract : Background: Despite effective combination antiretroviral therapy, HIV-infected individuals develop comorbidities, including cardiovascular disease, where activated macrophages play a key role. To date, few therapies target activated monocytes and macrophages. Methods: We evaluated a novel oral form of the polyamine biosynthesis inhibitor methylglyoxal-bis-guanylhydrazone (MGBG) on cardiovascular inflammation, carotid artery intima–media thickness (cIMT), and fibrosis in a simian immunodeficiency virus infection model of AIDS. Eleven simian immunodeficiency virus–infected animals received MGBG (30 mg/kg) once daily and 8 received a placebo control both beginning at 21 days postinfection (dpi). Animals were time sacrificed at 49 days post infection (dpi), when their matched placebo controls developed AIDS (63, 70, 77, 80), or at the study end-point (84 dpi). Aorta, carotid artery, and cardiac tissues were analyzed. Quantitative analyses of macrophage populations and T lymphocytes were done and correlated with cIMT and fibrosis. Results: MGBG treatment resulted in 2.19-fold (CD163 + ), 1.86-fold (CD68 + ), 2.31-fold (CD206 + ), and 2.12-fold (MAC387 + ) decreases in macrophages in carotid arteries and significant 2.07-fold (CD163 + ), 1.61-fold (CD68 + ), 1.95-fold (MAC387 + ), and 1.62-fold (CD206 + ) decreases in macrophages in cardiac tissues. cIMT (1.49-fold) and fibrosis (2.05-fold) also were significantly decreased with MGBG treatment. Numbers of macrophage and the degree of fibrosis in treated animals were similar to uninfected animals. A positive correlation between decreased macrophage in the carotid artery and cIMT, and cardiac macrophages and fibrosis was found. Conclusions: These data demonstrate that directly targeting macrophages with MGBG can reduce cardiovascular inflammation, cIMT, and fibrosis. They suggest that therapies targeting macrophages with HIV could be used in conjunction with combination antiretroviral therapy.